Design of Low-Cost Single-Layer 2-Bit Reflective Programmable Metasurface Based on Folded Ground - Li, Puchu; Ren, Jian; Chen, Yongji; Ren, Xuenan; Xu, Kai-Da; Yin, Ying-Zeng; Shen, Ming (IEEE transactions on microwave theory and techniques, 2023)
A low-cost single-layer 2-bit programmable metasurface (PM) is proposed in this article. This PM is processed on a single-layer printed circuit board (PCB) with the microwave structure, ground, and bias lines, enabled by a folded ground. The folded ground design moves a part of the ground from the bottom to the top layer to leave an area for bias lines. Vias are used to connect the ground in top and bottom layers to form a whole. The bias line in the microwave structure area is grounded by two capacitances to isolate microwave current with the bias line area. An asymmetric patch is designed in microwave area as the 2-bit microwave structure. To verify the microwave performance of this PM, functions of generating double beams, electromagnetic (EM) waves with orbital angular momentum (OAM), and a high gain beam are simulated. The far-field pattern of a 16×16 PM antenna in beam scanning is measured. The measured results show that the PM antenna has a beam scanning capability of ±60° and a maximum aperture efficiency of 44.6%. Finally, to illustrate the universality of the folded ground design, the varactor-loaded continuous phase adjustable PM and variable polarization 1-bit PM are discussed.